Towards Inclusive, Participatory Peer Tutor Development in Higher Education - Clarence, Sherran (Critical Studies in Teaching and Learning, 2023)
Peer  tutoring  has  a  long  history  in  academic  support  spaces  in  universities,  such  as  writing centres  and  supplemental  instruction  programmes. Small  group  peer  tutoring  has  moved increasingly into ‘mainstream’ teaching and learning, and has become an academic necessity in these spaces. The nature of student-tutor engagements in these spaces is about sharing and co-constructing  knowledge,  and  developing  more  independent  student  learners.  Yet,  tutor development and training tends to under-prepare peer tutors to create participatory, inclusive tutorial environments. This paper argues for tutor development itself to model participatory, inclusive ,and  development  practices,  such  that  tutors  learn  from  being  part  of  the training process how to improve their practice. Drawing on qualitative data from a three-year project at  a  traditional, historically  black South  African  university,  this  paper  shows  how  such  an approach yields benefits for tutors that include building knowledge about tutoring that overtly includes  tutors’  existing  knowledge  and  experiences.  Ultimately,  a  more  inclusive  approach to  tutor  development  has  a  strong  likelihood  of  changing  tutoring  praxis,  making  tutorials more participatory, inclusive, and shared spaces for learning.